2006
DOI: 10.2353/ajpath.2006.050533
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Protein Kinase CK2 in Astroglial Cells of Normal and Neovascularized Retina

Abstract: We previously documented protein kinase CK2 involvement in retinal neovascularization. Here we describe retinal CK2 expression and combined effects of CK2 inhibitors with the somatostatin analog octreotide in a mouse model of oxygen-induced retinopathy (OIR). CK2 expression in human and rodent retinas with and without retinopathy and in astrocytic and endothelial cultures was examined by immunohistochemistry, Western blotting, and reverse transcriptase-polymerase chain reaction. A combination of CK2 inhibitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 67 publications
1
53
1
Order By: Relevance
“…Later on, it was tested whether the effect of CK2 inhibitors would be enhanced if they were contributed with other anti-angiogenic drugs with a different mode of action. A significant increase in inhibition of angiogenesis was observed with a combination of the somatostatin analogue octreotide in combination with TBB [67]. In a subsequent study, it was shown that bone marrow derived human stem cells injected into the vitreous of neonatal mice can incorporate into the retinal neovasculature.…”
Section: Ck2 and Angiogenesismentioning
confidence: 88%
See 1 more Smart Citation
“…Later on, it was tested whether the effect of CK2 inhibitors would be enhanced if they were contributed with other anti-angiogenic drugs with a different mode of action. A significant increase in inhibition of angiogenesis was observed with a combination of the somatostatin analogue octreotide in combination with TBB [67]. In a subsequent study, it was shown that bone marrow derived human stem cells injected into the vitreous of neonatal mice can incorporate into the retinal neovasculature.…”
Section: Ck2 and Angiogenesismentioning
confidence: 88%
“…Not only does CK2 inhibition results in the induction of apoptosis in various cancer cells, but, as presented here, it additionally becomes evident that CK2 inhibition also leads to a retarded or blocked angiogenesis. Moreover, combination therapies with CK2 inhibitors and other drugs such as octreotide was shown to be significantly more efficacious in inhibiting retinal neovascularisation than either drug alone [67]. Another study has also shown a synergistic blocking effect on ocular neovascularisation by inhibitors of VEGF and PEDF-B signalling [72].…”
Section: Ck2 and Angiogenesismentioning
confidence: 91%
“…Early reports describing the use of CK2 inhibitors in vivo in mouse models, in which no evident toxicity has been observed, supported this notion. 55,56 Most importantly, very recently a phase-I clinical trial started in USA, sponsored by Cylene Pharmaceuticals, which is testing safety, tolerability and highest dose level of the CK2 inhibitor CX-4945 in patients with advanced solid cancers, Castleman's disease or MM (NCT00891280). Preliminary results have displayed very encouraging results, 46 and later a myeloma-dedicated phase-I trial has started (NCT01199718).…”
Section: The Therapeutic Potential Of Ck2 Inhibition In Blood Tumorsmentioning
confidence: 99%
“…Remarkably, protein kinase CK2 regulates the expression of COX2 and drives retinal neovascularization. 22 The PGE2 may induce angiogenesis by acting indirectly on a variety of cell types to produce proangiogenic factors. Indeed, PGE2 stimulation of airway smooth muscle, 23 endometrium, 7 or colon 8 cancer cells leads to increased production of VEGF, bFGF, or CXCL1 that, in turn, act on target endothelial cells to promote the angiogenesis.…”
Section: Pge2 Regulates Angiogenesis 5361mentioning
confidence: 99%